PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS (TWO STAY TWO STRAY) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 008 LUBUK SIAM - Dasir, Syaiful; Marhadi, Hendri; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was conducted to improve learning outcomes IPS Elementary School fourth grade students 008 Lubuk Siam. It can be seen from 23 the number of students there were 7 (30.43%) of students who reach the limit KKM and 16 (69.56%) declared not complete the assigned school KKM is 69. The average value of grade 56.7. The purpose of this research to improve learning outcomes IPS with the implementing cooperative learning model TSTS (Two Stay Two Stray) in the fourth grade students of SD Negeri 008 Lubuk Siam. The results of this study after study conducted, obtained an average value of 70.2 UH I increased with the percentage of 23.81% and the UH II average value increased to 80.4 percentage increased to 41.79%. Once applied cooperative learning model TSTS (Two Stay Two Stray) in the first cycle increased with the percentage of 56.52% in the classical is not finished, while in the second cycle there peningkatandengan percentage of 82.60 classically been completed. Activities teachers in the first cycle of the first meeting of the percentage of 70.83% categorized enough activity. The second meeting increased with 79.16% percentage has increased with both categories. At the first meeting of the second cycle of the activities of teachers has increased the percentage of activity 87.5% with both categories. At the second meeting of the second cycle has been increased with the percentage of 91.66% with a very good category. Activities of students in the first cycle the first meeting of the percentage of 70.83% categorized enough activity. The second meeting with a percentage of 79.16% has been increased with both categories. At the first meeting of the second cycle of student activity has increased the percentage of activity 87.5% with both categories. A second meeting has been increased with the percentage of 91.66% with a very good category, thus the implementation of cooperative learning model TSTS (Two Stay Two Stray) can improve student learning outcomes IPS.Keywords: TSTS (Two Stay Two Stray) Learning Outcomes